Mathematics competition (Algebra and Discrete Mathematics, 2007)
The Shevchenko Scientific Society of America and U.S.-Ukraine Foundation are sponsoring an annual mathematics competition for young mathematicians in Ukraine. The winner of the competition will be awarded a prize of 5000 USD. The goal of the competition is to help young mathematicians who are working at research institutions in Ukraine, and to stimulate the interest of young people in pure and applied science. The competition is open to citizens of Ukraine who are working permanently in Ukraine, 35 years old, or younger, and who posses the degree of Kandydat, or D.Sc., in physico-mathematical sciences